Ponto de Acesso, V. 3, N. 2, (ago) 2009 (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
link de acesso ao número: http://www.portalseer.ufba.br/index.php/revistaici/issue/view/368